2014
DOI: 10.1177/0022034514525200
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Interplay between NFIC and TGF-β1 in Apical Papilla-derived Stem Cells

Abstract: While transforming growth factor-β1 (TGF-β1) can regulate odontoblast differentiation in tooth crown morphogenesis, its effects on cells including stem cells from the apical papilla (SCAPs) involved in root formation are unclear. Nuclear factor I-C (NFIC) has been implicated in the regulation of root development, and interplay with TGF-β1 signaling has been reported in some cell types. We hypothesize that NFIC and TGF-β1 are important to the behavior of SCAPs and that the interplay between these molecules cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Similar stimulation of ALP at a lower TGF-b1 concentration and inhibition of ALP at a higher concentration is also noted in osteoblasts (45)(46)(47)(48) and pulp cells (data not shown) (31). However, TGF-b1 was found to inhibit the ALP activity of SCAPs cultured in mineralizing differentiation medium (36). Accordingly, Shirakawa et al (5) studied the ALP activity of pulp cells; in 1 pulp cell strain, TGF-b1 stimulated ALP activity at 0.1 ng/mL and decreased it at 5 ng/mL.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar stimulation of ALP at a lower TGF-b1 concentration and inhibition of ALP at a higher concentration is also noted in osteoblasts (45)(46)(47)(48) and pulp cells (data not shown) (31). However, TGF-b1 was found to inhibit the ALP activity of SCAPs cultured in mineralizing differentiation medium (36). Accordingly, Shirakawa et al (5) studied the ALP activity of pulp cells; in 1 pulp cell strain, TGF-b1 stimulated ALP activity at 0.1 ng/mL and decreased it at 5 ng/mL.…”
Section: Discussionsupporting
confidence: 67%
“…Chan et al (29) also found that TGF-b1, TGF-b2, and TGF-b3 slightly inhibited (about 20%) the growth of human dental pulp cells in the presence of 10% fetal serum. TGF-b1 inhibits the growth of SCAPs cultured in mineralizing differentiation medium (36), possibly because of its content of dexamethasone (37). On the contrary, exposure to TGF-b1 (1-5 ng/mL) increased the DNA content of human pulp cells in the presence of 10% serum (5).…”
Section: Discussionmentioning
confidence: 99%
“…Nfic signaling modulates Tgfβ signaling via dephosphorylation of phosphoSmad2/3 during late odontoblast differentiation, maturation and mineralization . Similarly, Nfic antagonizes the effects of Tgfβ1 on stem cells from the apical papilla (SCAPs) in vitro (He et al, 2014).…”
Section: Bmp/tgfβ Signalingmentioning
confidence: 99%
“…TGF-β can up-regulate NGF in hDPSCs via p38 and JNK MAPK pathways [ 58 ]. Some studies suggest that TGF-β1 can inhibit the proliferation of SCAPs and their mineralization by decreasing the osteogenic/dentinogenic gene expressions [ 59 ]. In detail, TGF-β1 promotes the cell growth, collagen content and ALP activity at lower concentrations (0.1-1 ng/mL) but down-regulates the activity at higher concentrations (>5 ng/mL) by regu lating ERK1/2 and Smad2 signaling pathways [ 60 ].…”
Section: Tgf-β Signaling Pathwaymentioning
confidence: 99%